IWR-1, a tankyrase inhibitor, attenuates Wnt/β-catenin signaling in cancer stem-like cells and inhibits in vivo the growth of a subcutaneous human osteosarcoma xenograft. (1st February 2018) - Martins-Neves, Sara R.; Paiva-Oliveira, Daniela I.; Fontes-Ribeiro, Carlos; Bovée, Judith V.M.G.; Cleton-Jansen, Anne-Marie; Gomes, Célia M.F.
Abstract: Wnt/β-catenin or canonical Wnt signaling pathway regulates the self-renewal of cancer stem-like cells (CSCs) and is involved in tumor progression and chemotherapy resistance. Previously, we reported that this pathway is activated in a subset of osteosarcoma CSCs and that doxorubicin induced stemness properties in differentiated cells through Wnt/β-catenin activation. Here, we investigated whether pharmacological Wnt/β-catenin inhibition, using a tankyrase inhibitor (IWR-1), might constitute a strategy to target CSCs and improve chemotherapy efficacy in osteosarcoma. IWR-1 was specifically cytotoxic for osteosarcoma CSCs. IWR-1 impaired spheres' self-renewal capacity by compromising landmark steps of the canonical Wnt signaling, namely translocation of β-catenin to the nucleus and subsequent TCF/LEF activation and expression of Wnt/β-catenin downstream targets. IWR-1 also hampered the activity and expression of key stemness-related markers. In vitro, IWR-1 induced apoptosis of osteosarcoma spheres and combined with doxorubicin elicited synergistic cytotoxicity, reversing spheres' resistance to this drug. In vivo, IWR-1 co-administration with doxorubicin substantially decreased tumor progression, associated with specific down-regulation of TCF/LEF transcriptional activity, nuclear β-catenin and expression of the putative CSC marker Sox2. We suggest that targeting the Wnt/β-catenin pathway can eliminate CSCs populations in osteosarcoma. Combining conventional chemotherapy with Wnt/β-catenin inhibition may ameliorate therapeutic outcomes, by eradicating the aggressive osteosarcoma CSCs and reducing drug resistance. Highlights: Wnt/β-catenin is specifically active in osteosarcoma cancer stem-like cells. Wnt inhibition induces apoptosis and cell cycle arrest of osteosarcoma CSCs. Wnt/β-catenin disruption impairs osteosarcoma stemness-related features. Wnt inhibition synergizes with doxorubicin against chemoresistant CSCs. IWR-1 abrogates Wnt/β-catenin activity and tumor burden in vivo .